Pengaruh Penetapan Standar Akuntansi Keuangan (Konvergensi IFRS) Terhadap Relevansi Nilai Informasi Akuntansi - Nurzi Sebrina; Salma Taqwa (Wahana Riset Akuntansi, 2017)
One of the key requirements for investors is a transparent accounting system. The Internatioanl Financial Acounting standards (IFRS) was introduced to improve the quality and accuracy of financial reporting. This study examines the effect of adopting IFRS on the value relevance of earnings, changes in earnings and book value information. A sample of 317 firms listed on the Indonesia Stock Exchange were purposively selected between 2011 and 2014. Data earnings, book value, return, was collected and tested using return model and price models. Because there's a problem of classical assumption test result data can be processed as much as 629 observation for return model and 1198 observation for price model. Hypothesis testing was done by using two models: Return Model and Price Model. The study shows that an increasing value relevance of earnings, changes in earnings and book value information took place during the early years of the application of the IFRS. The value relevance of book value was higher than the value relevance of earnings and changes in income, which shows the book value of information is important information for investors. While the value relevance of earnings information increased during the application of international accounting standards, the value relevance of changes in earnings information decreased